La utilización del cuento para el desarrollo del lenguaje en los niños y niñas de 2 a 3 años del Centro Infantil del Buen Vivir Gotitas de Miel de la ciudad de Guaranda, provincia Bolívar, periodo lectivo 2018-2019 - Azas Aldas, Jessica Natali (2018)
In the children's stage, stories are a primordial tool because children observe, manipulate and listen to them, developing language better, learning new words, using their imagination, changing the plot, replicating the reading with friends, the educator and at home. In the children's center, the use of stories is not essential since the educator does not use it in a pedagogical way, in the children's room from 2 to 3 years old, stories are scarce because the parents are of low economic resources for that reason does not collaborate for the purchase of this material, the few that there are not appropriate for the age that they have bone of 2 to 3 years, since they are extensive and with few images, in addition the location of the stories must be in the corner of reading so that children notice what does not happen in the children's center because it has them in a drawer. A children's story is perfect to enhance the habit of reading in children from 2 to 3 years. The educator when telling a story must have different materials and relate in different ways so that the children can understand better and then the child can repeat the story. For children to enjoy storytelling it is necessary to do it at the right time, so that the child rests, pays attention, enjoys and lives each scene; replicate it with your friends, cousins or relatives imitating the rapporteur, using new vocabulary and improving their expression. In the Children's Center Gotita de Miel, the problem for which the project was carried out was evidenced, for the reason that there are many children who do not want to talk, in order to get everyone to clearly express themselves as future nursery teachers, we carry out several activities using the story as for example: we tell stories in different ways so that the child is interested and can understand better, we use implements when telling a story, we tell a story with large images, etc. At the end of the project all children from 2 to 3 years of the Children's Center Gotita de Miel have improved the language, use new words and communicate more easily